Effects of Lactate on One Class of Group III (CT3) Muscle Afferents - Peterson, Rochelle A.; König, Christine; Zimmermann, Katharina; Barry, Christine M.; Wiklendt, Lukasz; Brookes, Simon J. H. (Frontiers in Cellular Neuroscience, 2020)
A class of Group III muscle afferent neurons has branching sensory terminals in connective tissue between layers of mouse abdominal muscles ("CT3 muscle afferents"). These sensory endings have recently been shown to be both mechanosensitive and metabosensitive. In the present study, responses of CT3 afferents to lactate ions and to changes in temperature were recorded. Raising muscle temperature from 32.7 to 37˚C had no consistent effects on CT3 afferent basal firing rate or responses to either von Frey hair stimulation or to applied load. Superfusion with lactate ions (15mM, pH7.4) was associated with an increase in firing from 6 ± 0.7 Hz to 11.7 ± 6.7 Hz (14 units, n=13, P < 0.05, P = 0.0484) but with considerable variability in the nature and latency of response between units. Reductions in concentrations of extracellular divalent cations, which mimicked the chelating effects of lactate, did not increase firing. Messenger RNA for the G-protein coupled receptor, hydroxyl carboxylic acid receptor 1 (HCAR1) was detected in dorsal root ganglia and HCAR1-like immunoreactivity was present in spinal afferent nerve cell bodies retrogradely labelled from mouse abdominal muscles. Some effects of lactate on afferent firing may be mediated by HCAR1.Striated muscle is innervated by multiple classes of sensory neurons with a range of properties. Specialised muscle spindles give rise to rapidly conducting Group I and II fibres. Group III and IV fibres are smaller in diameter, with slower conduction and largely encode metabosensitive and nociceptive signals from muscle. A class of group III mechanosensitive afferents were recently shown to have metabosensitive endings in the connective tissue layers closely associated with muscle fibres and were referred to as "CT3" afferents. They also show saturating responses to low levels of muscle stretch and can be potently activated by a metabolite mix comprising adenosine triphosphate (ATP),